Vernalization Responses in Onion (Allium cepa) Pre-flowering and Reproductive Phases - Yalamalle, V. R. (International Journal of Bio-resource and Stress Management, 2016)
The present study was aimed at determining the effect of augmented vernalization on the seed yield and seed yield contributing characters of onion seed crop. The experiment consisted of in vitro augmented vernalization at three different temperatures 0±0.5 °C, 5 ± 0.5 °C and 10±0.5 °C for durations 10, 20, 30 or 40 days and two levels of GA3 at 500 PPM and 1000 PPM in two short day onion varieties- Bhima Kiran and Bhima Super. Bulbs stored at 10 °C for 10 days and 0 °C for 30 days pre-planting produced plants that flowered 11.64 days and 6.44 days earlier than non-vernalized plants in variety Bhima Kiran and Bhima Super respectively. Augmented vernalization resulted in increase of number of scape plant-1. Kharif harvested variety Bhima Super had highest increase in flowering (56%) where as rabi harvested variety Bhima Kiran variety reported 30 % increase in flowering over control. Bulb treatment with GA3 did not increase the flowers nor yield, majority of the plants appeared showed stunted growth. Indicating the non suitability of GA3 as a bulb treating hormone. Bulbs stored at 10 °C for 10 days and 0 °C for 30 days gave the highest seed yield in variety Bhima Kiran and Bhima Super respectively. Seed quality parameters except for 1000 seed weight were not affected by the vernalization treatments. From the present study it is concluded that short duration cold treatment of 10 °C for 10 days enhances the seed yield in onion.